Organizational and law aspects of the development of the insurance market in Ukraine - Оlena Kuzmak; Yurii Svereda (Економічний форум)
Insurance is an integral element of the financial system of any state. Changes taking place in society, Ukraine's strategic course for integration into the European Union, and the world community are becoming a determining factor of organizational and legal transformations in the country, including issues of further development of the insurance market. The main goal of the study is to assess the organizational and legal aspects of the development of the insurance market in Ukraine. The systematization of literary sources and approaches to solving this problem showed that the issue of the development of the insurance market in Ukraine is relevant. The urgency of solving this scientific problem lies in the fact that updating the legislation that will regulate the insurance market will bring positive changes in the development of the insurance market of Ukraine. The study of the problem was carried out in the following logical sequence: first, the main problems and perspectives of the introduction of new legislation regulating the insurance market of Ukraine were analyzed. The methodological tools of the research were the following approaches and methods: a systematic approach, logical generalization, and comparison, methods of analysis and synthesis - to assess the main aspects of changes in legislation. Based on the analysis of the regulatory regulation of the insurance market of Ukraine, one of the main goals of the law and the future activity of the insurance market is to ensure its financial stability and transparency, as well as to regulate the activities of its subjects (insurers, insurance intermediaries, providers of auxiliary services), to reduce the risk of non-compliance financial obligations assumed by them. It should be noted that by the agreement between Ukraine and the European Union, the new law takes into account the main requirements of EU directives. The results of the study can be useful in terms of developing methods for improving the organizational and legal aspects of the development of the insurance market of Ukraine. It is proposed to introduce an insurance or financial ombudsman institute to protect the rights of consumers of insurance services